Open to New Light Quaker Spirituality in Historical and Philosophical Context. - Stevenson, Leslie (Luton : Andrews UK, 2011)
This book is about "the meaning of life" or "the spiritual quest". It offers a selective and critical evaluation of some central strands of Western religious and philosophical thought over two and a half thousand years. It starts with Socrates' philosophy of life, and the Greek tradition of philosophy that he initiated. It gives its own "take" on the teaching of Jesus, and on the long and controversial history of Christianity. There is a chapter devoted to George Fox and the beginning of ...
Metaphorical realism in theology?Resurrection?; Dogma and openness in religion; What is resurrection of the body supposed to be?; The resurrection of Jesus?; Resurrection as spiritual renewal; Wittgenstein and an epistemology of love?; Back Matter; Also Available
Description based upon print version of record.
Keywords: Religions -- Philosophy; Spiritual life -- Society of Friends; Quakers -- Conduct of life; RELIGION / Christian Life / General; Electronic books